Modern approaches to the treatment of vulvovaginal candidiasis - N V Artymuk; V I Chernyaeva (IP Berlin A.V., 2015)
The review presents the current data on the approach to the management of vulvovaginal candidosis (VVC). It is shown that the main current trend in the management of acute VVC is the use of short courses of antifungal therapy with a local application of azole. Fenticonazole is currently the drug of choice in the treatment of VVC has a high efficiency and safety.